Monkeypox in Pakistan-First case report - Akhtar, Nasim (Journal of the Pakistan Medical Association, 2024)
Monkeypox (mpox) is an uncommon zoonotic contagious viral ailment, resulting from the poxvirus. Symptoms include fever, headache, muscle aches, and a characteristic rash. There is no specific treatment, and only a limited number of antiviral drugs and vaccines are available. Employing stringent contact and respiratory precautions is essential to curb disease transmission. Till April 17, 2023, no mpox cases have been reported from Pakistan. Here we present the case of a 41-year-old male with a travel history to Saudi Arabia and a week-long history of multiple nodular and pustular eruptions on various parts of the body. It is essential to emphasise that due to its infrequency, a high index of clinical suspicion is imperative in facilitating an accurate diagnosis. Keywords: mpox, MPXV, Pakistan, Travel history. Orthopoxvirus. Vaccine.